Предмет: Алгебра,
автор: Anonim44455512
СРОЧНО!!!!!!!!!!!!!!!!!!!!!!
Приложения:
Ответы
Автор ответа:
1
Ответ:
Объяснение:
(a-b²)(a+b²)=a²-(b²)²=a²-b^4
(2a³b-1)(2a³b+1)=(2a³b)²-1²=4a^6b²-1
(a²b+5)(5-a²b)=5²-(a²b)²=25-a^4b²
(2a-3b)(2a+3b)=(2a)²-(3b)²=4a²-9b²
(a-2)²-(a-3)(a+3)=(a-2)²-(a²-9)=a²-4a+4-a²+9=13-4a
(a^4-2b)(a^4+2b)-a³(a-b²)=a^8-4b²-a^4+a³b²
a^8- означает а( в 8 степени)
Похожие вопросы
Предмет: Математика,
автор: kba1
Предмет: Химия,
автор: Летаргия888
Предмет: Химия,
автор: OmaN54
Предмет: Математика,
автор: ника2826
Предмет: Обществознание,
автор: 562048922